2018
DOI: 10.1016/j.watres.2018.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Ozonation control and effects of ozone on water quality in recirculating aquaculture systems

Abstract: To address the undesired effect of chemotherapeutants in aquaculture, ozone has been suggested as an alternative to improve water quality. To ensure safe and robust treatment, it is vital to define the ozone demand and ozone kinetics of the specific water matrix to avoid ozone overdose. Different ozone dosages were applied to water in freshwater recirculating aquaculture systems (RAS). Experiments were performed to investigate ozone kinetics and demand, and to evaluate the effects on the water quality, particu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
19
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 45 publications
1
19
0
2
Order By: Relevance
“…Exogenous ROS may come from various sources, and their impacts on redox status have consequences on cell viability, activation, proliferation, and organ function. Farmed fish encounter an increased flow of exogenous ROS several times during a lifetime, as many husbandry practices employ ROS-generating compounds either as a form of disinfectant or water treatment, or as a chemotherapeutant [7][8][9][10][11]. The antimicrobial activity of ROS towards opportunistic and pathogenic microorganisms underlines their use in providing fish with a favourable rearing environment [12].…”
Section: Introductionmentioning
confidence: 99%
“…Exogenous ROS may come from various sources, and their impacts on redox status have consequences on cell viability, activation, proliferation, and organ function. Farmed fish encounter an increased flow of exogenous ROS several times during a lifetime, as many husbandry practices employ ROS-generating compounds either as a form of disinfectant or water treatment, or as a chemotherapeutant [7][8][9][10][11]. The antimicrobial activity of ROS towards opportunistic and pathogenic microorganisms underlines their use in providing fish with a favourable rearing environment [12].…”
Section: Introductionmentioning
confidence: 99%
“…It is highly unstable, making it a potent oxidizing agent with high germicidal effectiveness and is thus ideal for use in water treatment. Ozone has been an integral component of RAS over the years, and the benefits on improved water quality, biosecurity and fish health are well documented [ 4 , 5 , 6 , 7 , 8 , 9 ]. This strong oxidant improves water quality by reducing organic matter, chemical oxygen demand, dissolved organic carbon, fine particulates, nitrite, water color or even hydrogen sulphide [ 4 , 7 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of ozone in brackish and seawater systems presents a challenge as ozone leads to the formation of byproducts (total residual oxidants (TROs)). Ozone dosage and control is still challenging due to limited options in measuring technologies for ozone and TROs [ 8 , 14 ]. Ozone measurements in industrial aquaculture facilities are often not standardized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence has occasionally been used for off-and online monitoring in water treatment applications to optimize processes [25] and to identify deteriorating agents [26]. It is able to determine rapidly and accurately DOM in aquatic environments [19,[26][27][28][29][30][31][32][33][34] total organic carbon (TOC) [33], biological oxygen demand (BOD) [35], phosphate, nitrogen-based compounds [36] and microbial abundances [37]. A recent study suggested a method to correlate the fluorescence degradation upon ozonation with the delivered ozone dosage in recirculating aquaculture systems [38].…”
Section: Introductionmentioning
confidence: 99%